A Study of Conceptual Metaphors and Their Schematic basis in Congenital Absolute Blinds and Their Counterparts Based on Embodied Cognition Theory - Elham Esmaeilpour Aghdam; Masoud Dehghan (̒Ilm-i Zabān, 2020)
As the conceptual system of the human mind, based on which human thought and action is formed, is metaphorical in its essence and rooted in the conceptual system of language, metaphor is considered as a salient category in linguistic studies. The present study investigates the embodiment pattern of conceptual metaphors in the congenital blind in comparison with their vision counterparts from cognitive semantics perspective based on Lakoff and Johnson’s (1980) conceptual metaphors. The present quantitative-qualitative study was comparatively done between two groups of blind people and their counterparts. A total of 48 male and female blind men and women with graduate and postgraduate education aged 18- 28 years were evaluated. The participants were asked to describe the 30 selected words based on Bitley and Peggy’s (1991) procedures. In so doing, the study initially investigated image schemas as the source domain in metaphorical mappings and then conceptual metaphors used by the participants. Results show that the blinds, due to lack of vision, use more lexical descriptions and far more image schemas than their counterparts. Moreover, postgraduate female blinds were reported as the most users of image schemas.